Citizenship Acquisition and National Belonging
X, 184 p.
Keywords: What does it take to become a citizen of a particular nation? Is it justified to restrict membership of a society, and if so, on what grounds? This book explores a series of pressing, controversial issues surrounding the acquisition of citizenship, in theory and practice.